Gellan gum-Ionic liquid membranes for electrochromic device application - Neto, M. J. (2015)
Biopolymer-based materials have been of particular interest and they are alternatives to synthetic polymers based on the decreasing oil resources. The polymer electrolytes were doped with choline-based IL N,N,Ntrimethyl- N-(2-hydroxyethyl)ammonium bis(trifluoromethylsulfonyl)imide ([N1 1 1 2(OH)][NTf2]), or Er (CF3SO3)3 or both. The polymer electrolytes were employed in the production of glass/ITO/WO3/electrolyte/ CeO2–TiO2/ITO/glass electrochromic devices (ECDs). The lowest onset temperature for the degradation of all the SPEs is at ~130 °C for the Gellan Er (CF3SO3)3 (10:1) this temperature range of stability is wide enough for a material to be applied as an electrolyte/separator component in electrochemical devices. The three ECDs displayed fast switching speed (ca. 15 s). Gellan [N1 1 1 2(OH)][NTf2] Er (CF3SO3)3 (5:1:10) exhibited an electrochromic contrast of 4.2% in the visible region, the coloration efficiency attained at 555 nm was 3.5 and 0.90 cm-2 C-1 in the “colored” and “bleached” states, respectively, and the open circuit memorywas 48 h. Preliminary tests performed with a prototype electrochromic device (ECD) incorporating WO3 as cathodic electrochromic layer, are extremely encouraging.